PENGARUH SELF COMPASSION DAN SELF IMAGE TERHADAP IDE BUNUH DIRI PADA MAHASISWA DI KOTA SEMARANG - Deafika Trisnanda Riesta; Mulya Virgonita Iswindari Winta; Erwin Erlangga (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Suicide is one of the causes of death in the world. According to WHO, the number of deaths due to suicide is about 800,000 people each year, or about 1 person every 40 seconds. Indonesia ranks fourth from countries in ASIA with suicides. Suicide is prevalent among teenagers. In this case, it can be said that college students are also classified into late adolescence to go into early adulthood. Adolescence is the most important period for personality development and integration. The importance of Self Compassion and Self Image influences the emergence of Suicidal Ideation. The population in this study is students in Semarang City. Sample using Purposive Sampling. This type of research is quantitative research, which uses 3 scales, namely the Self Compassion scale, the Self Image scale and the Suicide Ideation scale. Data analysis techniques using SPSS. The results showed that the value of F Value calculated = 85.726 > Ftable = 8.562, this means that Self Compassion (X1) simultaneously affects Suicide Ideation (Y). F value count = 126.646 > Ftable = 8.562, This means that Self Image (X2) simultaneously affects Suicide Ideation (Y). Keywords: Self Compassion, Self Image, Suicide Ideation, Student